Maternal Ideas About Child Competence in Two Cultural Groups of the Indian Society. (September 2022) - Mishra, R. C.
This article examines the differences and similarities in the conception of child competence held by mothers of the Adivasi 1 and non-Adivasi cultural groups of Indian society. Two hundred mothers, 100 from each group, who had a school-going child between 7 and 8 years of age (range = 6.5 – 8.5 years), served as respondents. The Adivasi mothers belonged to the Kharwar group, whereas the non-Adivasi mothers were all Hindus and belonged to Yadav and Bania caste groups. Respondents from both groups lived in the same villages. A mother's conception of 'competence' was assessed by asking each mother to imagine a child of 7–8 years who she thought was 'doing well' and then point out the domains in which the child was 'doing well'. It was found that mothers of both groups considered physical and social domains significant to the same degree. The non–Adivasi mothers, more than the Adivasi mothers, used cognitive competence to conceptualise competence, while the Adivasi mothers emphasised, emotional and self-related domains for defining competence. Certain important differences within the sub-domains of each of the five main domains between the two groups were also found. Differences in defining child competence between Adivasi and non-Adivasi mothers are understood in terms of parental ethno-theories and eco-cultural approach.